Exploring the Social and Emotional Representations Used by the Elderly to Deal With the COVID-19 Pandemic - Eiguren, Amaia; Idoiaga, Nahia; Berasategi, Naiara; Picaza, Maitane (Frontiers in Psychology, 2021)
Spain has become one of the European epicenters of the COVID-19, a pandemic that particularly affects the elderly, since this group accounts for the majority of hospitalized cases and has the highest mortality rates. Therefore, the aim of this research is to understand how elder people represent and emotionally cope with COVID-19. Using a qualitative methodology a free association exercise elicited by the word “coronavirus” was completed by 115 participants (age range: 60-85 years) from the North of Spain. To analyze the content lexical analysis was used. Results revealed that elder people are worried because of the risk of the pandemic. Even though, most of the participants represent the risk as being associated with people older than themselves. In addition, both the Government and the mass media are criticized for failing to communicate a clear message, and for giving out information that is both insufficient and contradictory. Due to these circumstances, negative emotions appear such as fear, nervousness, uncertainty, restlessness and insecurity. Emotions of solitude and loneliness also emerged, and these are represented as being linked to death. These results indicate the need for Governments to manage the current situation with the elderly by placing greater emphasis on social and inclusive policies to help alleviate the possible effects of the pandemic and the lockdown.